(untitled) (Academicia Globe: Inderscience Research, 2022)
The aim of the work was to provide optimal characteristics of sports motivation for young kurash wrestlers, which should be considered as the management of sports motivation in the annual cycle of training. The participation of kurash wrestlers in competitions and the results of such performances can have a significant impact on sports motivation.